Cost-effectiveness of healthy eating and/or physical activity promotion in pregnant women at increased risk of gestational diabetes mellitus: economic evaluation alongside the DALI study, a European multicenter randomized controlled trial - Karen Broekhuizen; David Simmons; Roland Devlieger; André van Assche; Goele Jans; Sander Galjaard; Rosa Corcoy; Juan M. Adelantado; Fidelma Dunne; Gernot Desoye; Jürgen Harreiter; Alexandra Kautzky-Willer; et al. (BMC, 2018)
Abstract Background Gestational diabetes mellitus (GDM) is associated with perinatal health risks to both mother and offspring, and represents a large economic burden. The DALI study is a multicenter randomized controlled trial, undertaken to add to the knowledge base on the effectiveness of interventions for pregnant women at increased risk for GDM. The purpose of this study was to evaluate the cost-effectiveness of the healthy eating and/or physical activity promotion intervention compared to usual care among pregnant women at increased risk of GDM from a societal perspective. Methods An economic evaluation was performed alongside a European multicenter-randomized controlled trial. A total of 435 pregnant women at increased risk of GDM in primary and secondary care settings in nine European countries, were recruited and randomly allocated to a healthy eating and physical activity promotion intervention (HE + PA intervention), a healthy eating promotion intervention (HE intervention), or a physical activity promotion intervention (PA intervention). Main outcome measures were gestational weight gain, fasting glucose, insulin resistance (HOMA-IR), quality adjusted life years (QALYs), and societal costs. Results Between-group total cost and effect differences were not significant, besides significantly less gestational weight gain in the HE + PA group compared with the usual care group at 35-37 weeks (−2.3;95%CI:-3.7;-0.9). Cost-effectiveness acceptability curves indicated that the HE + PA intervention was the preferred intervention strategy. At 35-37 weeks, it depends on the decision-makers' willingness to pay per kilogram reduction in gestational weight gain whether the HE + PA intervention is cost-effective for gestational weight gain, whereas it was not cost-effective for fasting glucose and HOMA-IR. After delivery, the HE + PA intervention was cost-effective for QALYs, which was predominantly caused by a large reduction in delivery-related costs. Conclusions Healthy eating and physical activity promotion was found to be the preferred strategy for limiting gestational weight gain. As this intervention was cost-effective for QALYs after delivery, this study lends support for broad implementation. Trial registration ISRCTN ISRCTN70595832. Registered 2 December 2011.